Motivational factors for academicians in private universities to participate in knowledge-sharing activities - Mansor, Zuraina; Saparudin, I. N. (Universiti Putra Malaysia Press, 2015)
Everybody can be part of knowledge-sharing activities, and this is especially true if we are referring to Higher Education Institutions (HEIs), where, in many situations, knowledge sharing can be seen to take place via natural activities. However, barriers and problems for knowledge sharing are also common. This is because some people think that their knowledge is valuable and important and are unwilling to share unless there are enough incentives. This study applies the Theory of Planned Behaviour (TPB) to explain knowledge-sharing behaviour among academic staff at selected private HEIs in Malaysia. The main objective of this study is to identify the motivation that influences knowledgesharing behaviour. A total of 110 respondents participated in answering this study's questionnaire. The findings revealed that knowledge-sharing behaviour among academic staff exists and is affected by different motivational factors such as organisational rewards and reciprocal benefit as extrinsic factors and self efficacy and enjoyment in helping other as intrinsic factors.